ECOSAR- A Tool for Analyzing Toxicity of Pollutants to Aquatic Life - Durge P.V.; Deshmukh Sagar (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
ECOSAR is a program that has been designed for the expert user. It is a menu driven and contents many functions to assist the user. The acute toxicity of a chemical to fish fresh water and salt water, water fleas and green algae has been the focus of the ECOSAR. Hence even before commencing the project if the chemical composition of the waste is known or studied, the impact of waste will be known to everyone. The process may be altered if the waste is harmful to aquatic life or ECOSAR even is able to helpful to post monitoring of the project within the frame. Environmental assessors, chemical manufacturers, chemical suppliers and other regulatory agencies have used ECOSAR to develop quantitative screening level toxicity profiles for fish, aquatic invertebrates, and green algae. The paper aims at presenting case study, how the aquatic life gets affected due to let out of pollutants from paper industries situated at Chandrapur, district of Maharashtra.